If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36=3(3+3n)
We move all terms to the left:
36-(3(3+3n))=0
We add all the numbers together, and all the variables
-(3(3n+3))+36=0
We calculate terms in parentheses: -(3(3n+3)), so:We get rid of parentheses
3(3n+3)
We multiply parentheses
9n+9
Back to the equation:
-(9n+9)
-9n-9+36=0
We add all the numbers together, and all the variables
-9n+27=0
We move all terms containing n to the left, all other terms to the right
-9n=-27
n=-27/-9
n=+3
| 33=8+5x | | 4(3+x)=9(x-2) | | 6x+3=-3x+36 | | 7-5x=35 | | 18-2y-7y=81 | | 3/10x-12=4/5x-5 | | n=81(46-37) | | 7x-3(2x-4)=4(2-x) | | x9+4=22 | | -5(7-4x)=45 | | 4/3b–11=25 | | |3x^2-2x|=|6-2x^2| | | |3x^2-2x|=|6-x^2| | | 6-6x=1-4x | | 81/n+32=46 | | 9x-2(2x-3)=6+5x | | 43=7-9x | | 4y-5=y | | -16=4x+4x | | -9x-2-10x-8=-72 | | -6k-5k=-11 | | 2+3n-4=-14 | | 3/10p+4=0.5 | | 8x/6=42 | | 3(2x)+1=15 | | x-7=6(5-6x)1 | | 0.25n-2=3/4 | | -1/4k=-5 | | 15+x=54+9x | | 3(x+6)=4(+5) | | 15=1-6x-x | | -0.375c—11=13 |